Visual symptoms in McCune-Albright syndrome – case report - Niwald, Anna; Budzińska-Mikurenda, Małgorzata; Rogozińska-Zawiślak, Agnieszka; Mikołajczyk, Wanda; Niwald, Marek; Grałek, Mirosława (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
McCune-Albright syndrome is a rare complex genetic disorder. It is diagnosed on the basis of bone lesions – fibrous dysplasia, accompanied by at least one additional symptom: hyperactivity of endocrine glands or cafe au lait skin spots. We present symptoms, clinical picture and diagnostic procedure in a 15-year old patient with visual disorders in the course of McCune-Albright syndrome. The ophthalmic disturbances were the part of described syndrome. The active behaviour of the ophthalmologist in multidisciplinary diagnostic procedure led to the establishment of a proper diagnosis and optimal treatment.